Vertebroplasty reduces progressive ׳creep' deformity of fractured vertebrae. Issue 6 (11th April 2016) - Luo, J.; Pollintine, P.; Annesley-Williams, D.J.; Dolan, P.; Adams, M.A.
Abstract: Elderly vertebrae frequently develop an "anterior wedge" deformity as a result of fracture and creep mechanisms. Injecting cement into a damaged vertebral body (vertebroplasty) is known to help restore its shape and stiffness. We now hypothesise that vertebroplasty is also effective in reducing subsequent creep deformations. Twenty-eight spine specimens, comprising three complete vertebrae and the intervening discs, were obtained from cadavers aged 67–92 years. Each specimen was subjected to increasingly-severe compressive loading until one of its vertebrae was fractured, and the damaged vertebral body was then treated by vertebroplasty. Before and after fracture, and again after vertebroplasty, each specimen was subjected to a static compressive force of 1 kN for 1 h while elastic and creep deformations were measured in the anterior, middle and posterior regions of each adjacent vertebral body cortex, using a 2D MacReflex optical tracking system. After fracture, creep in the anterior and central regions of the vertebral body cortex increased from an average 4513 and 885 microstrains, respectively, to 54, 107 and 34, 378 microstrains (both increases: P <0.001). Elastic strains increased by a comparable amount. Vertebroplasty reduced creep in the anterior and central cortex by 61% ( P =0.006) and 66% ( P =0.017) respectively. Elastic strains were reduced by less than half this amount. Results suggest that the beneficial effects of vertebroplasty on the vertebral body continue long after the post-operative radiographs. Injected cement not only helps to restore vertebral shape and elastic properties, but also reduces subsequent creep deformation of the damaged vertebra.